Optimising Early Childhood Educational Settings for Health Using Nature-Based Solutions: The Microbiome Aspect - Jake M. Robinson; Alexia Barrable (MDPI AG, 2023)
Early childhood is a time of rapid physiological, cognitive, and social development, affected by various environmental factors. The physical environment, including the environmental microbiome (the entire consortium of microorganisms and their theatre of activity in a given environment), plays an essential role in childhood development and can be shaped in ways to support health and wellbeing. In this Perspective article, we present considerations for early childhood education settings that wish to shape their outdoor and indoor environments to optimise human and ecosystem health. This is done in line with the latest evidence base on optimising health-supporting interactions between humans and environmental microbiota, but also in pedagogically and developmentally appropriate ways. Based on the Microbiome-Inspired Green Infrastructure (MIGI) principles, the considerations presented here not only support health through human-nature interactions and a healthier natural environment, but also promote a closer, reciprocal relationship between children and their natural environments.